2008
DOI: 10.1158/0008-5472.can-08-0400
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts Isolated from Common Sites of Breast Cancer Metastasis Enhance Cancer Cell Growth Rates and Invasiveness in an Interleukin-6–Dependent Manner

Abstract: Common sites of breast cancer metastasis include the lung, liver, and bone, and of these secondary metastatic sites, estrogen receptor A (ERA)-positive breast cancer often favors bone. Within secondary organs, cancer cells would predictably encounter tissue-specific fibroblasts or their soluble factors, yet our understanding of how tissue-specific fibroblasts directly affect cancer cell growth rates and survival remains largely unknown. Therefore, we tested the hypothesis that mesenchymal fibroblasts isolated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
190
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(205 citation statements)
references
References 50 publications
12
190
1
2
Order By: Relevance
“…In addition, other groups showed that CM from CAFs has a growth-promoting effect on tumor cells due to factors secreted in the culture medium (14,15). Among these factors, IL-6, TGFbeta, COX-2, and CXCL14 have already been mentioned (16)(17)(18)(19)(20). Interestingly, we show that our results are in accordance with Erez et al in that the proinflammatory gene signature was up-regulated in our fibroblasts in vitro as well, except for SPP1, which showed down-regulation upon tumor cell confrontation (21).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, other groups showed that CM from CAFs has a growth-promoting effect on tumor cells due to factors secreted in the culture medium (14,15). Among these factors, IL-6, TGFbeta, COX-2, and CXCL14 have already been mentioned (16)(17)(18)(19)(20). Interestingly, we show that our results are in accordance with Erez et al in that the proinflammatory gene signature was up-regulated in our fibroblasts in vitro as well, except for SPP1, which showed down-regulation upon tumor cell confrontation (21).…”
Section: Discussionsupporting
confidence: 92%
“…Stromal cells, a crucial component of the tumors milieu, are a major source of inflammatory mediators. 5,12,34 Here, we found that in breast CAF and in normal mammary gland fibroblasts (NF), NRs agonists downregulate NF-kBLuc and IL6Luc promoter activity (Figure 4a). In CAF, NRs agonists reduce the expression of a variety of inflammatory cytokines that promote MS formation, [5][6][7][8][9][10][11][12] namely IL6, IL8 and TNFa (Figure 4b).…”
Section: Effects Of Nuclear Receptors On Breast Cancer Stem Cells a Pmentioning
confidence: 74%
“…[5][6][7][9][10][11][12]34 Stromal cells are crucial components of the tumors milieu and are a major source of inflammatory mediators. 5,12,34 Here, we are able to show an NRs dependent downregulation of pro-inflammatory cytokines expression in CAF, and a concomitant reduction of their capability to sustain MS formation. Our data therefore suggest that the in vivo action of NRs on CSCs may involve a co-operative effect of their anti-inflammatory activity on tumor stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies have demonstrated that fibroblasts-derived matrix metalloproteinases 26 and cytokines such as vascular endothelial growth factor, 8 stromal cell-derived factor-1, 9 and IL-6, 7 enhanced epithelial tumor growth and progression by using tumor transplantation models. However, whether the results are unique for transplanted tumors is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors secreted by fibroblasts, such as epidermal growth factor, hepatocyte growth factor, and interleukin-6 (IL-6), can stimulate cancer cell proliferation and enhance their invasive properties. 6,7 Others, such as vascular endothelial growth factor, stromal cell-derived factor-1, and matrix metalloproteinases, can promote angiogenesis. 8 -10 Fibroblast-derived cytokine IL-1 and chemokine (C-X-C motif) ligand 14 have been shown to play vital roles as immune modulators.…”
mentioning
confidence: 99%